2018
DOI: 10.21521/mw.6037
|View full text |Cite
|
Sign up to set email alerts
|

Fascioloides magna: a parasite of roe deer in Bory Zielonogórskie

Abstract: The aim of this study was to determine the prevalence of infection with F. magna flukes in roe deer from the conifer forest Bory Zielonogórskie. Parasitological dissection was performed on 20 roe deer hunted in May 2016. Faecal samples from the animals were examined by the decantation method. One roebuck was verified to be infected with F. magna, which yielded a prevalence of 5%. We noted fibrinous deposits on the diaphragmatic surface of the liver with adhesions to the diaphragm, as well as five dark-coloured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
2
6
0
1
Order By: Relevance
“…The fascioloidosis foci known to exist in Europe continue to expand ( 11 , 23 ), and this was reflected in our study. The prevalence of infection in the studied area was found to significantly increase from 2014 to 2016 and 2017, and previous studies of cervids in the Lower Silesian Wilderness confirmed a similar trend of parasite expansion to new hosts and territories ( 5 , 8 , 26 ). Two key environmental risk factors for F. magna infection are soil type and the possibility of flooding and water accumulation, both of which favour the presence of the intermediate host ( 13 ); furthermore, parasite spread may be exacerbated by the growing population of cervids in the Lower Silesian Wilderness, integral to which are the recent introduction of fallow deer and the increasing popularity of deer farming ( 8 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The fascioloidosis foci known to exist in Europe continue to expand ( 11 , 23 ), and this was reflected in our study. The prevalence of infection in the studied area was found to significantly increase from 2014 to 2016 and 2017, and previous studies of cervids in the Lower Silesian Wilderness confirmed a similar trend of parasite expansion to new hosts and territories ( 5 , 8 , 26 ). Two key environmental risk factors for F. magna infection are soil type and the possibility of flooding and water accumulation, both of which favour the presence of the intermediate host ( 13 ); furthermore, parasite spread may be exacerbated by the growing population of cervids in the Lower Silesian Wilderness, integral to which are the recent introduction of fallow deer and the increasing popularity of deer farming ( 8 ).…”
Section: Discussionsupporting
confidence: 78%
“…This movement causes excessive tissue damage and severe haemorrhage, which often bring about the death of the animal (16). However, recent reports of fascioloidosis in roe deer have indicated the presence of juvenile trematodes in the liver parenchyma and of adults in the pseudocysts producing eggs (5,13); this could reflect a potential adaptation of roe deer to survive F. magna infection. As such, roe deer should also be considered to play a potential role in F. magna transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of the C. elaphus between the two existing foci (southwest and southeast areas), the spread of the infected aquatic snails, and the larval forms of the parasite in the watercourses and rivers make F. magna infection a threat to cervids and domestic ruminants in Poland [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, necropsy investigation of the carcasses did not detect pseudocyst formation [3,7,15] or egg production [72] in roe deer. Currently, increasing amounts of evidence confirm that in roe deer, pseudocyst development [91], egg production [82,83] and egg shedding [92] are common phenomena in endemic areas of Europe.…”
Section: The Special Role Of Roe Deermentioning
confidence: 99%
“…Among potential definitive hosts in Europe, roe deer is the only one with a solitary lifestyle. These animals live, feed, and drink in a limited territory; they encounter their conspecifics during the mating season, so the acquisition of infection is incidental [82,91]. In different areas, a very diverse prevalence can be detected.…”
Section: The Special Role Of Roe Deermentioning
confidence: 99%